Network Prominence, Bargaining Power, and the Allocation of Value Capturing Rights in High-Tech Alliance Contracts - Ozmel, Umit; Yavuz, Deniz; Reuer, Jeffrey J.; Zenger, Todd (Organization Science, 2017)
We suggest and provide empirical evidence that the bargaining power of alliance partners stemming from their prominence in alliance networks influences the ex-ante allocation of value capturing rights in high-tech alliance contracts. Network prominence can enhance the availability of alternative partners for a firm and thereby elevates the firm’s bargaining power and enables the firm to receive (i) more value capturing rights vis-à-vis its partner (i.e., more net value capturing rights) and (ii) more rights to the unexpected outcomes vis-à-vis its partner. We empirically investigate the content of research and development (R&D) collaboration contracts between biotech and pharmaceutical firms and show that as the prominence of the client (i.e., pharmaceutical firm) increases, it is able to attain (i) more net value capturing rights to outcomes within the area of collaboration and (ii) more rights to unexpected outcomes. By contrast, increased prominence of the R&D firm (i.e., biotech firm) decreases both the number of net value capturing rights the client receives as well as the rights to unexpected outcomes that the client captures in an alliance contract. The bargaining power that the R&D firm attains from its prominent position in alliance networks becomes less important during hot IPO markets, which provide the R&D firm more outside options to obtain financial resources. By documenting the importance of firms’ network positions as sources of bargaining power during alliance contracting, our paper contributes to the literature on strategic alliances, bargaining, and contract design.